The Network of Interactions Between Classical Swine Fever Virus Nonstructural Protein p7 and Host Proteins - Fan, Jindai; Zhang, Mengru; Liu, Chenchen; Zhu, Mengjiao; Zhang, Zilin; Wu, Keke; Li, Zhaoyao; Li, Wenhui; Fan, Shuangqi; Ju, Chunmei; Yi, Lin; Ding, Hongxing; et al. (Frontiers in Microbiology, 2020)
Classical swine fever (CSF) is a highly contagious viral disease causing severe economic losses to the swine industry. As viroporins of viruses modulate the cellular ion balance and then take over the cellular machinery, blocking the activity of viroporin or developing viroporin-defective attenuated vaccines offers new approaches to treat or prevent viral infection. Nonstructural protein p7 of CSF virus (CSFV) is a viroporin, which was highly involved in CSFV virulence. Deciphering the interaction between p7 and host proteins will aid our understanding of the mechanism of p7-cellular protein interaction affecting CSFV replication. In the present study, seven host cellular proteins including microtubule-associated protein RP/EB family member 1 (MAPRE1), voltage-dependent anion channel 1 (VDAC1), proteasome maturation protein (POMP), protein inhibitor of activated STAT 1 (PIAS1), gametogenetin binding protein 2 (GGNBP2), COP9 signalosome subunit 2 (COPS2), and contactin 1 (CNTN1) were identified as the potential interactive cellular proteins of CSFV p7 by using yeast two-hybrid (Y2H) screening. Plus, the interaction of CSFV p7 with MAPRE1 and VDAC1 was further evaluated by co-immunoprecipitation and GST-pulldown assay. Besides, the p7-cellular protein interaction network was constructed based on these seven host cellular proteins and the STRING database. Enrichment analysis of GO and KEGG indicated that many host proteins in the p7-cellular protein interaction network were mainly related to the ubiquitin-proteasome system, cGMP-PKG signaling pathway, calcium signaling pathway, and JAK-STAT pathway. Overall, this study identified potential interactive cellular proteins of CSFV p7, constructed the p7-cellular protein interaction network, and predicted the potential pathways involved in the interaction between CSFV p7 and host cells.